Medida da espessura e ecogenicidade do ramo direito do diafragma crural em pacientes com doença do refluxo gastroesofágico - Nobre, Rivianny Arrais (2014)
Width and ecogenicity of the diaphragm right crus in patients with gastroesophageal reflux disease. RIVIANNY ARRAIS NOBRE. Tese (Doutorado). Programa de Pós-Graduação Stricto Sensu em Ciências Médicas. Orientador: Professor Doutor Miguel Ângelo Nobre e Souza. Gastroesophageal reflux disease (GERD) patients may be better identified by the inspiratory pressure of the lower esophageal sphincter (LES), which is lower, than the expiratory one, and symptoms may be alleviated by inspiratory muscle training. Three groups of human volunteers were selected for this study. Twenty patients with reflux esophagitis (ESOPHAGITIS), nine patients with symptoms of GERD but no esophagitis (NES), and eleven asymptomatic volunteers (Control Group). The volunteers answered GERD and quality-of-life related questionnaires, and underwent endoscopic ultrasound examination and high resolution manometry. The main goal was to study the gastroesophageal junction (GEJ) and the crural diaphragm (CD) in particular (right crus). The width of the CD right crus was measured in millimeters. A standard segment of the CD was analyzed for the average grey intensity of its pixels, and this was taken for ecogenicity. The CD width was thinner in the ESOPHAGITIS group relative to Controls (CD width mean: 3.45 ± 0.24 mm versus 5.19 ± 0.48 mm, p = 0.0077). CD ecogenicity was greater in the ESOPHAGITIS patients relative to Controls (mean ecogenicity: 32.38 ± 2.45 versus 18.35 ± 2.53, p = 0.0009). These findings suggest that some ESOPHAGITIS patients may have an atrophic CD with a greater fat or fibrosis content. There is a decreasing CD width across the ESOPHAGITIS, NES, and control groups. However, this finding was only significant between the ESOPHAGITIS and the Controls. The LES average pressure during resting was similar between the ESOPHAGITIS and Control groups. However, the LES minimal respiratory pressure, IRP, the LES maximal residual pressure, the mean wave amplitude at 3 and 7 cm above the LES, and the maximal DCI were smaller in the ESOPHAGITIS patients relative to controls. The more heartburn bothered the ESOPHAGITIS patients the thinner was the CD width (r = -0.5559, p = 0.0166). The findings of this study point to a possible CD atrophy in some patients with reflux esophagitis. These are in accordance with previous functional studies and set the stage for new studies about GERD physiopathology and the relationship between the diaphragm and esophageal diseases.